Clinical and histologic features of botryoid odontogenic cyst: A case report - Farina, Vitor H. [UNESP]; Brandão, Adriana A.H. [UNESP]; Almeida, Janete D. [UNESP]; Cabral, Luiz A.G. [UNESP] (Springer Nature, 2010)
Introduction. The lateral periodontal cyst, as the name implies, occurs on a lateral periodontal location and is of developmental origin, arising from cystic degeneration of clear cells of the dental lamina. A botryoid odontogenic cyst is considered to be a rare multilocular variant of a lateral periodontal cyst. Case presentation. We report the clinical and histopathologic features of a rare case of botryoid odontogenic cyst found in an edentulous area corresponding to the right lower canine of a 64-year-old African-American woman. A multilocular radiolucency was observed, and surgical removal of the lesion revealed a nodule of rubber-like consistency measuring about 1.5 cm in diameter. Cross-sectioning of the nodule showed that it consisted of various cystic compartments. Histologically, various voluminous periodic acid-Schiff-negative clear cells randomly distributed throughout the cystic epithelium were observed, as well as cell layers showing thickenings generally formed by oval, sometimes entangled plaques. The capsule consisted of fibrous connective tissue and showed rare and discrete foci of a perivascular mononuclear inflammatory infiltrate and reactive bone-tissue fragments. The final diagnosis was botryoid odontogenic cyst. Conclusion: We provide data that allow the reader to establish the differences between botryoid odontogenic cyst, glandular odontogenic cyst, and lateral periodontal cyst, helping with the differential diagnosis. The reader will have the opportunity to review botryoid odontogenic cyst clinical and histopathologic features, including treatment. © 2010 Farina et al; licensee BioMed Central Ltd.
Keywords: adult; bone tissue; case report; cellular distribution; clinical examination; connective tissue; edentulousness; embryonal rhabdomyosarcoma; female; histopathology; human; inflammatory infiltrate; odontogenic cyst; periodontal disease; priority journal